Spiritualisme Ratu Kalinyamat: Kontroversi Tapa Wuda Sinjang Rambut Kanjeng Ratu di Jepara Jawa Tengah - Said, Nur (el Harakah: Jurnal Budaya Islam, 2013)
In Javanese tradition, patriarchal culture is hold strongly though it cannot be generalized as a necessity. The emergence of Queen Kalinyamat as the representation of Javanese woman apparently indicates a contrary to the mainstream Javanese tradition. This article is a semiotical analysis on the spiritualism of Queen Kalinyamat who lived in the 16th century and protested against injustice in that time. She sent the military forces to Malacca to repel the Portuguese so that she was known as a wealthy and very powerful woman. Meanwhile, when her husband and brother were killed by Arya Penangsang, she also demanded justice by living as a naked ascetic (tapa wuda sinjang rambut) which resulted in multiple spiritual interpretations for grass root society. This is mostly interpreted as the spirit of sex drive, but the sufis interpreted it as meaningful metaphor to leave all sorts of worldly power material and position, then it is symbolized by the Arabic letter of Alif. Naked in this case is as a symbol of self-emptying and then filled with repentance, love and taqorrub to God. Queen Kalinyamat’s spiritualism counters the Javanese tradition toward different perspective reflecting eco-feminism trend in post-colonial era. Dalam tradisi Jawa, budaya patriarki masih sangat kuat meskipun tidak bisa digeneralisasi sebagai suatu keniscayaan. Munculnya Ratu Kalinyamat sebagai representasi perempuan di Jawa, ternyata menunjukkan kondisi bertentangan dengan tradisi Jawa secara umum. Artikel ini melalui analisis semiotik membahas spiritualisme Ratu Kalinyamat di Jepara, Jawa Tengah yang hidup di abad ke16 dan berani protes terhadap ketidakadilan pada waktu itu. Dia mengirimkan armada pasukan militer ke Malaka untuk mengusir penjajah Portugis hingga dikenal sebagai wanita kaya dan sangat kuat. Sementara itu, ketika suami dan kakaknya dibunuh Arya Penangsang, dia juga menuntut keadilan dengan bertapa telanjang (tapa wuda sinjang rambut) yang telah melahirkan multi-makna spiritual di masyarakat akar rumput. Meskipun sebagian memaknainya sebagai semangat gairah seksual, kalangan sufistik memandangnya sebagai perilaku simbolik yang bermakna meninggalkan segala macam kekuasaan duniawi baik material dan jabatan sehingga dilambangkan dengan huruf Arab Alif. Telanjang dalam hal ini sebagai simbol pengosongan diri dan kemudian diisi dengan pertobatan, kasih dan taqorrub kepada Allah. Spiritualisme Ratu Kalinyamat menentang tradisi Jawa yang cenderung patriarki menuju perspektif yang berbeda yang mencerminkan trend ecofeminisme di era poskolonial.